Complete Radiologic Response of Metastatic Pancreatic Ductal Adenocarcinoma to Microwave Ablation Combined with Second-Line Palliative Chemotherapy - Hakon Blomstrand; Karin Adolfsson; Per Sandström; Bergthor Björnsson (Case Reports in Gastrointestinal Medicine)
Pancreatic ductal adenocarcinoma (PDAC) has a bleak prognosis, especially for the majority of patients diagnosed with metastatic disease. The primary option for palliative treatment is chemotherapy, and responses beyond first-line treatment are rare and typically short. Here, we report a case of a 63-year-old woman with PDAC in the head of the pancreas who was initially successfully treated by pancreaticoduodenectomy followed by adjuvant chemotherapy with gemcitabine. However, disease recurrence with liver and para-aortic lymph node metastases was detected only two months after the completion of adjuvant chemotherapy. First-line palliative chemotherapy with gemcitabine-nab/paclitaxel was commenced. The results were discouraging, with disease progression (liver and lung metastases) detected at the first evaluation; the progression-free survival was just two months (64 days). Surprisingly, the response to second-line palliative chemotherapy with 5-fluorouracil-oxaliplatin was excellent; in combination with the ablation of a liver metastasis, this treatment regimen resulted in a complete radiological response and an 11-month treatment-free interval with a sustained good performance status.